Development and optimization of analytical methods for rapid detection of multiple mycotoxins in wheat products and dietary risk assessment - Kuan-Hsun Li; Mei-Jen Huang; Tomohisa Ogawa; Tseng-Yu Tsai; Hong-Da Hua; Deng-Jye Yang (Food Chemistry, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Biomechanical Evaluation of Zygomatic Implants: Intrasinus vs. Parasinus Surgical Approaches - Yu-Ling Wu; Aaron Yu-Jen Wu; Jui-Ting Hsu; Heng-Li Huang (Journal of Medical and Biological Engineering, 2026)

O, S, C isotopic signatures of high-arsenic groundwater in Ngari, Xizang: Seasonal-scale drivers of arsenic release mechanisms - Lian Song; Shehong Li; Jen-How Huang; Fei He; Qiao Han; Jie Liao; Zhenjie Zhao; Ci Ren Qu Ji; Yong Shui (Acta Geochimica, 2026)

Hybrid apoptotic body decorated supramolecular hydrogel system for melanoma cancer immunoediting - Wei-Yuan Huang; Nai-Wen Liang; Li-Jen Yu; Chen-Hsiang Kuan; Chien-Wen Chang; Tsung-Chiao Wu; Yu-Tso Liao; Tzu-Wei Wang (Chemical Engineering Journal, 2025)

Unleashing instant on-site naked-eye detection by a portable NIR-SPR platform with organic upconversion - Li-Chen Su; Xin-Hui Wang; Chun-Jen Shih; Zhi-Hao Huang; Ying-Feng Chang; Chen-Kai Chang; Chi-Yun Wang; Yu-Ching Huang; Shun-Wei Liu (Chemical Engineering Journal, 2025)

Pediatric Abdominal and Pelvic CT Scans and the Subsequent Risk of Malignancy and Benign Genital Tumors: A Retrospective Cohort Study - Feng-Yi Su; Chih-Feng Chen; Kevin Chih-Yang Huang; Cheng-Li Lin; Fuu-Jen Tsai; Jui-Ting Hsu; Shin-Lei Peng (Journal of Medical and Biological Engineering, 2025)

Avian reovirus induces autophagy-mediated cargo of progeny viruses to extracellular vesicles and enhancement of virus release - Chao-Yu Hsu; Wei-Ru Huang; I.-Hsun Chiang; Jyun-Yi Li; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Community metabolism and greenhouse gas emissions in abandoned tropical salt pans - Shu-Yen Huang; Wei-Jen Lin; Li-Hua Lee; Hsing-Juh Lin (Estuarine, Coastal and Shelf Science, 2025)

Biomass energy for a sustainable Taiwan: Technologies, policies, and future prospects - Yu-Wei Lin; Yu-Ting Liu; Li-Cheng Huang; Shing-Chou Lin; Shean-Jen Chen; YongMan Choi (Biomass and Bioenergy, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Nuclear translocation of β-catenin and migration of arecoline-induced oral cancer cells reduced by Taiwanin E via p-GSK3β downregulation - Chi-Cheng Li; Marthandam Asokan Shibu; Wei-Wen Kuo; Yueh-Hsiung Kuo; Yun-Peng Chao; Chun-Hsu Yao; Da-Tian Bau; Pei-Jei Lio; Chung-Jen Chiang; Chih-Yang Huang (Molecular & Cellular Toxicology, 2025)

Groundwater health risks and water quality assessment in the sources of many mighty rivers in Asia: Ngari, Tibet - Fei He; Shehong Li; Lian Song; Qiao Han; Dan Zeng Ya Jie; Yong Shui; Jen-How Huang (Process Safety and Environmental Protection, 2025)

Epidemiological investigation and analysis of human papillomavirus infection and cataract development - Jing-Xing Li; Shu-Bai Hsu; Yu-Han Huang; Fuu-Jen Tsai (VirusDisease, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

The Ecological Niches and Interspecific Associations of the Dominant Fishes in the Xiamen Seas, China - Liang-Min Huang; Hao-Qi Xu; Jia-Yue Yu; Yong-He Chen; Jia-Qiao Wang; Fen-Fen Ji; Jun Li; Jian-Di Cai; Ta-Jen Chu (Fishes, 2024)
Fish are vital in enhancing the stability of marine ecosystems. Therefore, understanding the ecological niches and interspecific correlation characteristics of their dominant species provides a good scientific basis for the protection and management of marine biodiversity. In this study, on the basis of survey data from trawls conducted in the waters off Xiamen in the spring (April) and autumn (November) of 2021, the ecotopes and interspecies connectivity of the dominant fish species were investigated using the relative importance index (IRI), χ2 tests, the association coefficient (AC), and Pearson and Spearman analyses. According to the IRI, there were 23 fish species with higher values, including 15 species in spring and 15 species in autumn. The 15 dominant fish species could be subdivided into wide-, medium-, and narrow-ecotope species, of which there were 2 and 3 wide-ecotope types in spring and autumn. The niche overlap indices exhibited a range of 0.000–0.809 in the spring and 0.000–0.915 in the autumn, showing small differences between the two seasons. The interspecific correlations between the dominant fishes in Xiamen’s waters in spring and autumn were weak, and both showed non-significant positive correlations, indicating that the correlations between the dominant fishes in this sea area are relatively independent. The findings of this investigation provide a fundamental database and theoretical framework for researching the adaptive mechanisms of marine fish in the Xiamen Seas.

Systematics and evolutionary dynamics of insect-fern interactions in the specialized fern-spore feeding Cuprininae (Lepidoptera, Stathmopodidae) - Zong-Yu Shen; Takeshi Terada; Jean-François Landry; Robert J.B. Hoare; Li-Yaung Kuo; Ming-Hsun Chou; Yu-Feng Hsu; Jen-Pan Huang (Molecular Phylogenetics and Evolution, 2024)

Temporal variability of air-water gas exchange of carbon dioxide in clam and fish aquaculture ponds - Veran Weerathunga; Li-Lian Liu; Fei-Ling Yuan; Sheng Xiang Xu; Kai-Jung Kao; Wei-Jen Huang (Science of The Total Environment, 2024)

Biophysical mechanisms underlying tefluthrin-induced modulation of gating changes and resurgent current generation in the human Nav1.4 channel - Hsing-Jung Lai; Ming-Jen Lee; Hsin-Wei Yu; Kuan-Wen Chen; Ke-Li Tsai; Pi-Chen Lin; Chiung-Wei Huang (Pesticide Biochemistry and Physiology, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Mitigating growth-stress tradeoffs via elevated TOR signaling in rice - Wei Li; Jiaqi Liu; Zeqi Li; Ruiqiang Ye; Wenzhen Chen; Yuqing Huang; Yue Yuan; Yi Zhang; Huayi Hu; Peng Zheng; Zhongming Fang; Zeng Tao; et al. (Molecular Plant, 2024)

Antimony isotopic fractionation during intensive chemical weathering of basalt in the tropics - Yunjie Wu; Guangyi Sun; Jen-How Huang; Haifeng Fan; Xinyu Li; Mengying Zhou; Yi Xia; Xinbin Feng (Geochimica et Cosmochimica Acta, 2024)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Origin and geochemical significance of antimony in Chinese coal - Xinyu Li; Guangyi Sun; Yunjie Wu; Mengying Zhou; Zhonggen Li; Xiangyang Bi; Jen-How Huang; Xinbin Feng (International Journal of Coal Geology, 2023)

Biomechanical Effects of Bone Atrophy, Implant Design, and Vertical or Tilted of Posterior Implant on All-on-Four Concept Implantation: Finite Element Analysis - Heng-Li Huang; Ting-Wei Lin; Hui-Ling Tsai; Yu-Ling Wu; Aaron Yu-Jen Wu (Journal of Medical and Biological Engineering, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Revealing the Effectiveness of Fisheries Policy: A Biological Observation of Species Johnius belengerii in Xiamen Bay - Liang-Min Huang; Jia-Qiao Wang; Yi-Jia Shih; Jun Li; Ta-Jen Chu (Journal of Marine Science and Engineering, 2022)
The rapid development of China’s economy has brought tremendous pressure to the marine ecosystem, and about 57% of marine fish populations have been overexploited or collapsed. A series of fisheries policies have been implemented successively to improve the decline of resources. Over the past decade, the fisheries sector has particularly increased focus on resource and ecosystem sustainability, which has led to the wider use of stock management policies in China. Therefore, fishery resource assessment is crucial, such as assessing the long-term changes in biological information. This study is based on biological characteristics of Johnius belengerii captured by bottom trawls in Xiamen Bay during two periods, beginning in 2006 and 2016. Length composition, length–weight relationship, growth, mortality, sexual maturation, and feeding intensity were analyzed. The changes in biological characteristics show that there is a phenomenon of improvement in the later period, of which the changes are closely related to a series of fisheries management strategies, such as setting closed fishing periods and non-fishing areas, and establishing fishery restoration marine protected areas. This result seems to reveal the effectiveness of a long-term series of fisheries policies. It can provide an important basis and visibility for management effectiveness.

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Evaluating the Effects Related to Restocking and Stock Replenishment of Penaeus penicillatus in the Xiamen Bay, China - Jia-Qiao Wang; Yi-Jia Shih; Liang-Ming Huang; Jun Li; Wei-Wen Li; Chun-Han Shih; Ta-Jen Chu (Journal of Marine Science and Engineering, 2021)
The quantitative evaluation of restocking and stock replenishment is essential for providing operational feedback and implementing adaptive management for future restoration projects. Since 2010, approximately 700 million juvenile shrimp (Penaeus penicillatus) have been released into Xiamen Bay, Fujian Province, China, each year, through stock replenishment programs. The recruited shrimp were sampled through three-year bottom trawl surveys from 2014 to 2017. The biological characteristics and catch equation were used to evaluate the effect of restocking and stock replenishment. The analysis uses the FAO-ICLARM Stock Assessment Tool (FISAT II) program. In general, there are two sources of recruitments—one from spawning brood stock and the other from released juvenile shrimp. We constructed an evaluation model for an effect evaluation based on Baranov’s catch equation to separate the initial recruitment volume using survey data. The relationship between body weight and total length was W = 1.638 TL2.9307. There is no statistically significant difference between males and females. The von Bertalanffy growth parameters derived for prawns, using FiSAT II, were L∞ = 209.6 mm and K = 0.51 per year. In spring 2014, the initial resource amount was 49,200, while the ratio of effective recruitment and parent amount was 3.92. The survival rate of the released shrimp larvae, 1.88‱, seems to be very unsatisfactory. The resource amount in summer and autumn is higher than in winter and spring. Obviously, the restocking effect is lower and the programs need to be improved. To improve the restocking effect, the replenishment performance should be adjusted to reduce the mortality rate and increase its release effectiveness. Therefore, corresponding implementations are recommended, including standard extensive culture, reduction in stress during transportation, and temporary culture.

Spatial and Structural Factors Shape Seagrass-Associated Bacterial Communities in Singapore and Peninsular Malaysia - Golam Rabbani; Bertrand Chengxiang Yan; Nicole Li Ying Lee; Jillian Lean Sim Ooi; Jen Nie Lee; Danwei Huang; Benjamin J. Wainwright (Frontiers in Marine Science, 2021)
Plant-microbe relationships play critical roles in the functioning and health of terrestrial plants, but little is known about this relationship in marine angiosperms such as seagrasses. Here, we investigated the microbial communities associated with the seagrass Enhalus acoroides throughout Singapore and Peninsular Malaysia. At each sampling location we collected 10 individual and unconnected plants. Each plant was subsequently broken down into leaves, roots, and rhizomes. In addition to living plant parts a sediment sample was taken in close proximity to each. Using high throughput 16S rRNA gene amplicon sequencing we characterised the bacterial communities associated with each plant part and the associated sediment sample. Results indicate geographic structuring of bacterial communities, with a significant pattern of distance decay suggesting dispersal limitation is a contributing factor to the differences we see in bacterial community structure. Bacterial communities can be further differentiated by the function of the collected sample (leaf, root, and rhizome), and we identified a number of microbial indicator species that are associated with each plant part. Further analysis revealed the presence of several microbial taxa that have previously been identified as indicators of “unhealthy” or “stressed” seagrass meadows. This study addresses a current scientific gap related to the characterisation of seagrass microbiomes, and provides a foundation on which future studies can build, particularly those in the Southeast Asian seagrass biodiversity hotspot.

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Chronic low dose of AM404 ameliorates the cognitive impairment and pathological features in hyperglycemic 3xTg-AD mice - Hei-Jen Huang; Shu-Ling Chen; Hsin-Yu Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Hsiu Mei Hsieh-Li; Ming-Tsan Su (Psychopharmacology, 2019)

Erratum to: Hypoxia Augments Increased HIF-1a and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Syun Hu; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2018)

Hypoxia Augments Increased HIF-1α and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2016)

Uptake and speciation of vanadium in the rhizosphere soils of rape (Brassica juncea L.) - Li-Yan Tian; Jin-Yan Yang; Jen-How Huang (Environmental Science and Pollution Research, 2015)

Partial Volume Correction for Equivocal Retropharyngeal Nodal Metastases of Nasopharyngeal Carcinoma with Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography - Yu-Wen Wang; Chin-Shun Wu; Chih-Han Chang; Kuo-Sheng Cheng; Yu-Kang Chang; I-Wen Huang; Chin-Li Lu; Wei-Jen Yao (Journal of Medical and Biological Engineering, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Genomic profiling of rice roots with short- and long-term chromium stress - Tsai-Lien Huang; Li-Yao Huang; Shih-Feng Fu; Ngoc-Nam Trinh; Hao-Jen Huang (Plant Molecular Biology, 2014)

Gelsolin (GSN) induces cardiomyocyte hypertrophy and BNP expression via p38 signaling and GATA-4 transcriptional factor activation - Wei-Syun Hu; Tsung-Jung Ho; Peiying Pai; Li-Chin Chung; Chia-Hua Kuo; Sheng-Huang Chang; Fuu-Jen Tsai; Chang-Hai Tsai; Yu-Chi Jie; Ying-Ming Liou; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Differential Legionella spp. survival between intracellular and extracellular forms in thermal spring environments - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Shih-Yung Hsu; Jen-Te Huang; Jorn-Hon Liu; Yu-Li Huang (Environmental Science and Pollution Research, 2013)

Comparison of early transcriptome responses to copper and cadmium in rice roots - Chung-Yi Lin; Ngoc Nam Trinh; Shih-Feng Fu; Yu-Chyuan Hsiung; Li-Chiao Chia; Chung-Wen Lin; Hao-Jen Huang (Plant Molecular Biology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

Activation of regulatory T cells instigates functional down-regulation of cytotoxic T lymphocytes in human breast cancer - Chao-Hsu Li; Wen-Hong Kuo; Wen-Chun Chang; Su-Cheng Huang; King-Jen Chang; Bor-Ching Sheu (Immunologic Research, 2011)

Micropropagation of bromeliad Aechmea fasciata via floral organ segments and effects of acclimatization on plantlet growth - Ping-Lung Huang; Li-Jen Liao; Chi-Chu Tsai; Zin-Huang Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Isolation of a 2-oxetanone from the fruits of Synsepalum dulcificum - Ming-Jen Cheng; Wen-Li Lo; Lee-Yu Huang; Chyi-Jia Wang; Chung-Yi Chen (Natural Product Research, 2010)

Isolation of a new monoterpenic ester from the leaves of Michelia compressa (Maxim.) Sargent var. formosana Kanehira (Magnoliaceae) - Ming-Jen Cheng; Wen-Li Lo; Jin-Cherng Huang; Yu-Ting Yeh; Zi-Ling Hong; Yu-Cheng Lu; Ming-Sung Chang; Chung-Yi Chen (Natural Product Research, 2010)

Effects of compressive residual stress on the morphologic changes of fibroblasts - Shu-Li Lin; Jen-Chang Yang; Kuo-Ning Ho; Chau-Hsiang Wang; Chien-Wu Yeh; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2009)

Polymorphisms in arsenic metabolism genes, urinary arsenic methylation profile and cancer - Chi-Jung Chung; Yu-Mei Hsueh; Chyi-Huey Bai; Yung-Kai Huang; Ya-Li Huang; Mo-Hsiung Yang; Chien-Jen Chen (Cancer Causes & Control, 2009)

Lipopolysaccharide upregulates uPA, MMP-2 and MMP-9 via ERK1/2 signaling in H9c2 cardiomyoblast cells - Yi-Chang Cheng; Li-Mien Chen; Mu-Hsin Chang; Wei-Kung Chen; Fuu-Jen Tsai; Chang-Hai Tsai; Tung-Yuan Lai; Wei-Wen Kuo; Chih-Yang Huang; Chung-Jung Liu (Molecular and Cellular Biochemistry, 2009)

Arsenic exposure, urinary arsenic speciation, and the incidence of urothelial carcinoma: a twelve-year follow-up study - Yung-Kai Huang; Ya-Li Huang; Yu-Mei Hsueh; Mo-Hsiung Yang; Meei-Maan Wu; Shu-Yuan Chen; Ling-I Hsu; Chien-Jen Chen (Cancer Causes & Control, 2008)

Isolation and characterization of the zebrafish Danio rerio insulin-like growth factor binding protein-3 promoter region - Ming Jun CHOU; Jian Chyi CHEN; Jyh Yih CHEN; Hong Yi GONG; Li Tzu LI; Tzou Chi HUANG; Jen Leih WU; Ching Ming KUO (Fisheries Science, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Independent [Ca2+]i increases and cell proliferation induced by the carcinogen safrole in human oral cancer cells - Jong-Khing Huang; Chun-Jen Huang; Wei-Chuan Chen; Shiuh-Inn Liu; Shu-Shong Hsu; Hong-Tai Chang; Li-Ling Tseng; Chiang-Ting Chou; Chih-Hung Chang; Chung-Ren Jan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

Molecular characterization of germline mutations in the BRCA1 and BRCA2 genes from breast cancer families in Taiwan - Steven Shoei-Lung Li; H.-M. Tseng; Tsui-Ping Yang; Chia-Han Liu; Shiuh-Jen Teng; Hung-Wen Huang; L.-M. Chen; Hsiao-Wei Kao; Jimmy H. Chen; Jau-Neng Tseng; Angela Chen; Ming-Feng Hou; et al. (Human Genetics, 1999)